The Impact of the GCC Boycott On Qatar Foreign Policy - Sri Wahyuni (Department of International Relations, Brawijaya University, 2017)
Seeing peace in the MENA (Middle East and North Africa) seems to be illusion. TheÂ 3rampant physical and ideological clashes fill up the news headline daily. The diplomatic crisis among Arab countries in particular Qatar and its neighbors is rooted since 1970 over borders dispute, and so then the Arab Spring phenomenon came up in addition to Qatarâ€™s Foreign Policy in which claimed by the opponent neighbor countries as a risk and security threat. The tension extends to the level of breaking off diplomatic relation between Qatar and UEA and its allies on 5th June 2017. The embargo prevailing on Qatar has profound significant impact in many aspects of both of Qatar and the GCC countries. Subsequent consequences and aftermath has been facing for both. The following pages will be outlining on foreign policy, precisely Qatar foreign policy after the boycott imposed by the GCC countries in 2017. Defining the term foreign policy and its function in international order can be found in the introduction part. Chapter one of the contents is the background of the GCC boycott on Qatar and what does the embargo mean for the GCC countries as well as Qatar. The impact of the blockade on Qatar foreign policy will be outlining in chapter two following with the conclusion of the topic discussed in the remaining pages.Key words: Boycott, Qatar, Foreign Policy